Evaluating the relationships among religion, social virtues, and meaning in life. (March 2019) - Krause, Neal; Hill, Peter C; Ironson, Gail
There is growing evidence that a sense of meaning in life may emerge, in part, from the social relationships that people maintain. But it is not clear how the relationship between social ties and a sense of meaning might arise. The purpose of this study is to see if meaning in life is associated with three socially focused virtues: compassion, forgiveness of others, and providing social support to others. In the process, an effort is made to see if these social virtues arise from social relationships in religious institutions. Two main findings emerge from a recent nationwide survey. First, people who are more compassionate, more forgiving, and who help others more often have a stronger sense of meaning in life. Second, individuals who receive more spiritual support from fellow church members are more likely to adopt these social virtues. The theoretical basis of these relationships is discussed.